1976
DOI: 10.1128/jvi.19.1.220-227.1976
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of tox mutants of corynebacteriophage beta

Abstract: Seventeen nontoxinogenic (tox) mutants of corynebacteriophage beta have been isolated by using a tissue culture screening technique. The mutants fall into four major classes. Two of the classes, I and II, appear to contain missense and nonsense mutants, respectively. However, classes III and IV have not been previously described. Class III mutants produce two proteins (CRMs) seriologically related to diphtheria toxin, but efforts to demonstrate the presence of more than one tox gene have not been successful. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…As illustrated in Figure 5, a linear relationship can be observed between AMFI values and cytotoxic activity of DT-IT to the TfnR, as well as to CD3 and to CD5 Ag in Jurkat cells. A relationship overlapping that obtained with DT-IT can also be observed when a mutant DT (CRM 107) lacking cell-surface-binding activity (Laird and Groman, 1976;Greenfield et al, 1987) is used instead of DT as the toxic component of anti-TfnR and anti-CD3 conjugates (Fig. 5).…”
Section: Correlation Of Amfi Values and Cytotoxic Eficacy Of Itsupporting
confidence: 56%
“…As illustrated in Figure 5, a linear relationship can be observed between AMFI values and cytotoxic activity of DT-IT to the TfnR, as well as to CD3 and to CD5 Ag in Jurkat cells. A relationship overlapping that obtained with DT-IT can also be observed when a mutant DT (CRM 107) lacking cell-surface-binding activity (Laird and Groman, 1976;Greenfield et al, 1987) is used instead of DT as the toxic component of anti-TfnR and anti-CD3 conjugates (Fig. 5).…”
Section: Correlation Of Amfi Values and Cytotoxic Eficacy Of Itsupporting
confidence: 56%
“…Whether nontoxinogenic strains of C. diphtheriae carry the tox gene in whole or in part is in itself a significant question for the epidemiology of diphtheria. Some time ago we reported the isolation of gamma nonconverting phage from a nontoxinogenic strain of C. diphtheriae (8), and we subsequently presented both genetic and physical evidence demonstrating the presence of all or part of the tox gene in this phage (2,12). From our data we concluded that nonexpression of the tox gene was due to the insertion of a piece of bacterial DNA either in a regulatory site or early in the structural gene for diphtheria toxin.…”
mentioning
confidence: 80%
“…Other mutational events such as point mutations, deletions, or inversions can also be invoked to explain the various phenotypes. Mutants have been produced artifically by nitrosoguanidine treatment of }-converting phage with phenotypes identical to those found naturally in the tox-, Tox-isolates (9,12,19). In addition to mutation in phage genes, it is clear that host gene mutations may also be responsible for variation in the expression of the tox gene (11).…”
Section: Infect Immun 54mentioning
confidence: 99%
“…A positive C7(p)t'ox control was streaked adjacent to each test culture so that a merger with the line for DT could be easily verified. The identity of this line with DT is based on the absence of any line when the isogenic, nontoxinogenic C7(-) is tested and on observations that some mutations in n-converting phage leading to the loss of toxin activity correlate with the loss of this line in the standard Elek test (18). Diphtheria antitoxin was obtained from the Connaught Laboratories, Inc. (Ontario, Canada).…”
mentioning
confidence: 99%